2021
DOI: 10.3389/fpsyg.2021.667271
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and Interoceptive Strength Norms for 270 French Words

Abstract: Perceptual experience through the five modalities (i.e., vision, hearing, touch, taste, and smell) has demonstrated its key role in semantics. Researchers also highlighted the role of interoceptive information in the grounded representation of concepts. However, to this day, there is no available data across these modalities in the French language. Therefore, the aim of this study was to circumvent this caveat. Participants aged between 18 and 50 completed an online survey in which we recorded scores of percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 78 publications
(175 reference statements)
2
20
0
Order By: Relevance
“…Data from the literature also showed that BOI and PS variables are strongly correlated with other semantic variables (i.e. concreteness, imageability, age of acquisition) that are known to affect word processing (Chedid et al, 2019;Juhasz & Yap, 2013 ;A Miceli et al, 2021;Miklashevsky, 2018;Pexman et al, 2019). Taken together, these studies are particularly relevant for appreciating the richness of conceptual representations and understanding how our knowledge is grounded.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Data from the literature also showed that BOI and PS variables are strongly correlated with other semantic variables (i.e. concreteness, imageability, age of acquisition) that are known to affect word processing (Chedid et al, 2019;Juhasz & Yap, 2013 ;A Miceli et al, 2021;Miklashevsky, 2018;Pexman et al, 2019). Taken together, these studies are particularly relevant for appreciating the richness of conceptual representations and understanding how our knowledge is grounded.…”
Section: Introductionmentioning
confidence: 81%
“…Fifty-five older participants with French as mother-tongue (37 women), aged between 65 and 89 (mean age= 74.38; SD= 4.93) with a socio-cultural level of high school (socio-cultural level= 4.16; four corresponding to high school 1 ) took part in this study and have completed the PS and BOI questionnaire. They were compared with 141 French-speaking young participants (100 women), aged between 18 and 50 (mean age= 25.75; SD= 7.43) with a socio-cultural level of higher education (socio-cultural level= 5.12; five corresponding to the bachelor level) from our PS previous study (A Miceli et al, 2021). The same young participants from this previous study also completed the BOI rating presented in the current study.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, there is no wide agreement on how to explain the semantic content of abstract language: is it based on perception and action experience, as Pulvermüller (2013; argues? Could it be based on an inner experience, such as interoception (Connell, Lynott and Banks, 2018;Miceli et al, 2021)? What if it is mostly based on linguistic and social experience (Borghi et al, 2018;Borghi et al, 2021)?…”
Section: Abstract Languagementioning
confidence: 99%